Seventy-five Years of Optometry Training - Beaulne, C (Canadian Journal of Optometry, 2021)
"Seventy-five years of Optometry Training - It's a Celebration". This was the title of my editorial in Vol. 6, No. 4 of "L'Optometriste"("The Optometrist"), the publication of the Quebec Association of Optometrists. In fact, 1985 marks a milestone that should be highlighted. It's the seventy-fifth anniversary of the founding of the University of Montreal's School of Optometry, and the sixtieth year of its affiliation with the University. I am therefore going to give a brief historical background of the only Francophone school of optometry in North America, discuss its current situation and its future projects at the dawn of the 21st century.